Upaya Meningkatkan Hasil Prestasi Belajar Guling Belakang Menggunakan Bidang Miring - Seno Purnomo; Agustina Sri Purnami (Media Manajemen Pendidikan, 2023)
This research is descriptive qualitative. Data collection techniques were obtained from observations, documentation and interviews with colleagues. Data analysis techniques with data collection, data reduction, data presentation and drawing conclusions. The results of observations made on class X Fashion 4 students of SMK Negeri 4 Yogyakarta in semester 1 (odd) of the 2022/2023 school year on July 8 2022 found several deficiencies in the implementation of back roll learning lessons, including the low ability of students in training back roll series, lots of movements that cannot be done perfectly (challenging to roll over, bent knees, starting point is not straight with the endpoint of the action, unsteady final attitude). The results of the assessment support this carried out, namely only 12 out of 28 students (42.86% of students) were able to obtain the results of the assessment above the KKM (Minimum Completeness Criteria) carried out. The results of research conducted using the method, modification of tools and facilities carried out by researchers together with collaborators, it can be concluded that: the use of an inclined plane in studying the motion of a series of back rolls with an initial standing attitude is effective in increasing the learning outcomes of students in class X Fashion 4 SMK N 4 Yogyakarta. The initial percentage of learning completeness before the action was 42.86% or only 12 out of 28 students were able to produce their learning outcomes (score ≥ 75), after the action research, the proportion of completeness students increased to 78.57% or 22 out of 28 students were able to complete their learning outcomes (grade ≥ 75), so that there is an increase in learning outcomes of 35.71%.